DEVELOPMENT OF INTERACTIVE POWERPOINT LEARNING MEDIA THEME 5 ECOSYSTEM SUBTHEME 1 ECOSYSTEM’S COMPONENT FOR FIFTH GRADE STUDENTS OF SDN 007 TEBING KARIMUN - Tisrin Maulina Dewi; Nurlaila; Edi Kurniawan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aims to know how the procedure for developing interactive powerpoint learning media and testing the feasibility of interactive powerpoint learning media products for fifth grade students of SDN 007 Tebing Karimun. This research was a research and development (R & D) with product development model Borg and Gall, modified as needed. Data on quality of product development were collected by questionnaire. Data analyzed with descriptive quantitative and qualitative techniques. The results of this study showed that: (1) the validation of material experts based on eligibility according to the subcomponent as a whole was in the criteria of 'very good / very feasible' (83%); (2) design expert validation according to the aspects assessed as being overall is in the criteria of 'very good / very feasible' (93%); (3) the response of the fifth grade teacher to the interactive powerpoint learning media developed was in the 'very good' criteria (96%); (4) trials that have been carried out, namely the initial field trials were in the 'very good' criteria (88%), small group field trials were in the 'very good' criteria (92%), while the limited field trials were in the criterion 'very good' (95%). This shows that the interactive powerpoint learning media theme 5 ecosystem subtheme 1 ecosystem’s component for fifth grade students of SDN 007 Tebing Karimun is feasible to be used as learning media in schools.